2022
DOI: 10.1370/afm.2846
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ and Patients’ Interruptions in Clinical Practice: A Quantitative Analysis

Abstract: PURPOSE Physicians' interruptions have long been considered intrusive, masculine actions that inhibit patient participation, but a systematic analysis of interruptions in clinical interaction is lacking. This study aimed to examine when and how primary care physicians and patients interrupt each other during consultations. METHODSWe coded and quantitatively analyzed interruption type (cooperative vs intrusive) in 84 natural interactions between 17 primary care physicians and 84 patients with common somatic sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Given the increased attention to patient-centred communication in medical curricula and the lay press, the available literature may therefore not represent current medical practice regarding the interruption of patients during their opening statement. Finally, the currently available literature on interruptions in medical consultations rarely distinguishes between different types of interruptions, which may be relevant because recent studies have shown that not all interruptions have a negative effect, [27][28][29][30] and that some interruptions may also have supportive and affirming functions in the consultation. [30][31][32] This study aimed to analyse hospital consultants' verbal interruption behaviour during the opening statement of their patients, considering various forms of interruptions and their effects on the doctor-patient consultation.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the increased attention to patient-centred communication in medical curricula and the lay press, the available literature may therefore not represent current medical practice regarding the interruption of patients during their opening statement. Finally, the currently available literature on interruptions in medical consultations rarely distinguishes between different types of interruptions, which may be relevant because recent studies have shown that not all interruptions have a negative effect, [27][28][29][30] and that some interruptions may also have supportive and affirming functions in the consultation. [30][31][32] This study aimed to analyse hospital consultants' verbal interruption behaviour during the opening statement of their patients, considering various forms of interruptions and their effects on the doctor-patient consultation.…”
Section: Open Accessmentioning
confidence: 99%
“…Finally, the currently available literature on interruptions in medical consultations rarely distinguishes between different types of interruptions, which may be relevant because recent studies have shown that not all interruptions have a negative effect, 27–30 and that some interruptions may also have supportive and affirming functions in the consultation. 30–32 …”
Section: Introductionmentioning
confidence: 99%
“… 1 The effects of sex and gender of patients are seen across symptoms, 2 diseases, 1 and throughout all phases of the patients’ illness trajectories. Differences between women and men are identified in the biopsychosocial etiology and persistence of somatic symptoms, 3 , 4 , 5 help-seeking behaviors, 6 medical communication about symptoms, 7 provided diagnostic interventions, 8 and efficacy of treatment. 9 …”
Section: Introductionmentioning
confidence: 99%